Hello
let : f(x) = 6 + √(14+x) - <span>√(9x)
f(2) = </span>6 + √(14+2) - √(9×2)
f(2) = 6 + √(16)-√(18)
f(2) = 6 + 4 - √(18) = 10 - √(18)
Answer:
The degree of the given expression is 2
Answer:
Step-by-step Yes it is, assuming we decide to use the Pythagorean Theorem to find the hypotenuse (10) it'll be possible considering the formula is c²=√a²+b²
(c being the longest side of the triangle)
a= 6 and b= 8
c² =√6² + 8²
c² = √100 square root of 100 equals 10
c= 10p explanation:
The area of the circle is
... A = (π/4)d² . . . . where d=10 in
The area of the square is
... A = d² . . . . . . . . where d=10 in
The amount of the square that is not in the circle is
... (1 -π/4)d² = 0.2146018d² ≈ 21.5 in² . . . for d=10 in